The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.optom.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refractive error on pupillary dynamics in the normal and mild traumatic brain injury (mTBI) populations

Abstract: PurposeThere have been several studies investigating static, baseline pupil diameter in visually-normal individuals across refractive error. However, none have assessed the dynamic pupillary light reflex (PLR). In the present study, both static and dynamic pupillary parameters of the PLR were assessed in both the visually-normal (VN) and the mild traumatic brain injury (mTBI) populations and compared as a function of refractive error.MethodsThe VN population comprised 40 adults (22–56 years of age), while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Although not specifically studies of PTH, prior studies have identified symptoms of dysautonomia among those with TBI . Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing . One such study showed head‐upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post‐concussion syndrome .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although not specifically studies of PTH, prior studies have identified symptoms of dysautonomia among those with TBI . Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing . One such study showed head‐upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post‐concussion syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…22,28,46 Studies of autonomic dysfunction following mTBI have assessed heart rate variability, 19 pupillary light reflex, arterial pulse wave, and graded exercise testing. 26,27,35 One such study showed head-upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post-concussion syndrome. 24 Another study showed a group of 8 patients who developed POTS based on head-upright tilt table test after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews 26 , 27 have highlighted the utility of portable pupillometry systems in a variety of fields including surgery, 26 , 28 critical care, and anesthesiology. 26 30 In large part, the value of these instruments is in their ability to quantitatively evaluate a physiological response that has previously been assessed by qualitative observations.…”
Section: Discussionmentioning
confidence: 99%